2023
DOI: 10.1007/s40520-023-02511-x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve weeks of combined physical and cognitive intradialytic training preserves alertness and improves gait speed: a randomized controlled trial

Špela Bogataj,
Maja Pajek,
Katja Kurnik Mesarič
et al.

Abstract: Background Hemodialysis (HD) patients often experience cognitive deficits and reduced mobility. While studies have shown promising results of physical and/or cognitive training in older adults, their effects in HD patients remain understudied. Aims This study aimed to evaluate the impact of a 12-week intradialytic training program combining cognitive training with physical exercise on attention domains and spontaneous gait speed (SGS) in HD patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…After the IDE intervention, absolute and relative changes in muscle function significantly differed by treatment status in patients aged from 60 to 70 years but did not differ in patients aged below 60 and over 70 years. Our findings regarding age heterogeneities partially align with previous reports on the effectiveness of IDE on lower extremity muscle function and physical functioning in age-diversified groups of HP, favouring patients age 60 and older Matsuzawa et al, 2017;Sánchez-Tocino et al, 2022;Bogataj et al, 2023). However, other studies reported no age-related differences in functional adaptation following IDE Uchiyama et al, 2021;Yabe et al, 2021).…”
Section: Impact Of a Patient´s Age Sex And Expression Of Microribonuc...supporting
confidence: 89%
“…After the IDE intervention, absolute and relative changes in muscle function significantly differed by treatment status in patients aged from 60 to 70 years but did not differ in patients aged below 60 and over 70 years. Our findings regarding age heterogeneities partially align with previous reports on the effectiveness of IDE on lower extremity muscle function and physical functioning in age-diversified groups of HP, favouring patients age 60 and older Matsuzawa et al, 2017;Sánchez-Tocino et al, 2022;Bogataj et al, 2023). However, other studies reported no age-related differences in functional adaptation following IDE Uchiyama et al, 2021;Yabe et al, 2021).…”
Section: Impact Of a Patient´s Age Sex And Expression Of Microribonuc...supporting
confidence: 89%
“…The results of the primary outcome measure, the Alertness score of the Test of Attentional Performance, were published in Bogataj et al. 22 In the current paper, focus is on the following outcome measures: TMT A and B (TMTA and TMTB), TUG test, and the TUG-dual. Other secondary outcome measures of the whole protocol were reported earlier 22 , 23 , 24 : Montreal Cognitive Assessment, Symbol Digit Modalities Test, 10 repetition sit-to-stand test, stork balance test, hand grip strength test, spontaneous gait speed, frailty, bioimpedance analysis, quality-of-life, brain derived neurotrophic factor, C-reactive protein, and interleukin-6.…”
Section: Methodsmentioning
confidence: 97%
“… 22 In the current paper, focus is on the following outcome measures: TMT A and B (TMTA and TMTB), TUG test, and the TUG-dual. Other secondary outcome measures of the whole protocol were reported earlier 22 , 23 , 24 : Montreal Cognitive Assessment, Symbol Digit Modalities Test, 10 repetition sit-to-stand test, stork balance test, hand grip strength test, spontaneous gait speed, frailty, bioimpedance analysis, quality-of-life, brain derived neurotrophic factor, C-reactive protein, and interleukin-6. The safety parameters were urea, creatinine, sodium, potassium, hemoglobin, hematocrit, self reported falls, and musculoskeletal injuries.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the pilot study on HD patients demonstrated that cognitive training and physical exercise separately prevented cognitive decline [ 29 ]. A growing number of studies on exercise training in the HD population show improvements in quality of life [ 30 , 31 ], body composition [ 32 ], inflammation [ 33 ], dialysis symptoms [ 34 , 35 ], and cognitive function [ 36 , 37 ]. Despite the previously mentioned positive impacts of physical exercise, there is a lack of randomized controlled trials that explore its effects on cognitive performance in HD patients.…”
Section: Introductionmentioning
confidence: 99%